Dependence on temperature of the electrical properties of nanocrystalline Y2Ti2O7 ceramics. Issue 5 (1st April 2018) - Joseph, Dona; Kaliyaperumal, Chitrarasu; Mumoorthy, Sashmeetha; Paramasivam, Thangadurai
Abstract: The nanocrystalline yttrium titanate (YTO) ceramic was prepared by polymerized sol-gel method. Structural analysis performed with x-ray diffraction and Raman spectroscopy showed the cubic-pyrochlore structure of YTO. Impedance and dielectric spectroscopy have been performed in a high temperature region varying from 550 to 700 °C. The YTO grains were found to participate dominantly in the process of electrical conduction. The YTO showed the negative thermal coefficient of resistance type material for electrical conduction. The dc conductivity of YTO followed the Arrhenius behavior and the activation energy was calculated to be 1.15 eV. The dielectric constant has increased with increasing the measuring temperature. The ac conductivity had shown the Universal behavior described by Jonscher's power law and the corresponding value of the frequency exponent ( n ) was found to be less than unity. The CBH model was successfully employed and the conduction was proved to occur through hopping mechanism and the value of maximum barrier height ( W M ) was obtained as 0.17 eV. Electrical modulus spectra were fitted with Bergman proposed KWW function and the dielectric relaxation occurred in YTO was of non-Debye type because the magnitude of stretching factor (β) was found to be less than unity (ranging from 0.77 to 0.89). The electrical modulus and impedance characteristics of YTO were properly scaled so that they fall in a single Universal plot, that implied that the respective mechanisms in the nanocrystalline YTO were reported to be temperature independent.